Programmatic access to bioinformatics tools from EMBL-EBI update: 2017 - Chojnacki, Szymon; Cowley, Andrew; Lee, Joon; Foix, Anna; Lopez, Rodrigo (Nucleic acids research, 2017)
Since 2009 the EMBL-EBI provides free and unrestricted access to several bioinformatics tools via the user's browser as well as programmatically via Web Services APIs. Programmatic access to these tools, which is fundamental to bioinformatics, is increasingly important as more high-throughput data is generated, e.g. from proteomics and metagenomic experiments. Access is available using both the SOAP and RESTful approaches and their usage is reviewed regularly in order to ensure that the best, supported tools are available to all users. We present here an update describing the latest enhancement to the Job Dispatcher APIs as well as the governance under it.